DAMPAK PERANG DAGANG AMERIKA SERIKAT-REPUBLIK RAKYAT TIONGKOK TERHADAP IMPOR PRODUK BAJA INDONESIA DARI TIONGKOK TAHUN 2018-2019 - Yesi Arnayati; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study describes the impact of the trade war between the United States and China on imports of Indonesian steel products from China, especially the impact on excess carbon steel entering Indonesia from China. The trade war began on March 8, 2018, when President Donald Trump set a policy of import tariffs on Chinese products. This policy had a negative impact on China and triggered an imbalance in China's foreign exchange earnings. So that China took action against it by setting import tariffs on several US products. The author collects data from books, academic journals, newspapers, theses and the internet related to the issue of the United States trade war with China and the impact of the trade war on imports of Indonesian steel products from China, the author uses a neorealism perspective and the level of analysis of the nation-state. The theory used in this study is the theory of trade barriers. The results showed that the effect of the trade war between the United States and China has resulted in China looking for other markets to market its excess domestic steel production. So imports of Indonesian alloy steel from China, spike in Indonesia's trade balance deficit against China,and the lossoff national steel industry especially in 2018-2019. Indonesia than took a series of policies to deal with the negative impact of imports off steel products from China, one of which was by issuing Trade Regulation Number 110 of 2018. Keywords: Trade War, Steel, Tariffs, Imports, Alloy Steel, Trade Regulation Number 110 of 2018.